Articulated Observance - Tom Grondona (Oz, 1988)
Never a crutch to start a project but always a useful tool narratives seem to appear at opportune times to solve the rainbow of problems encountered during the process of architecture. I have used them to tum a house into a medieval urban space, a sidewalk into a stage, a sushi bar into theatre and a house into furniture..